2019
DOI: 10.17770/sie2019vol4.3746
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Self-Reported Physical Activity Questionnaires Indicators

Abstract: “Global action plan on physical activity 2018–2030” emphasizes the need for weekly moderate physical activity for ensuring human health. Physical activity can be measured by a variety of objective and subjective methods, but one of the prerequisites for understanding the connection between active lifestyle and health certainty that the measuring instrument measures the feature for which it has been created and that it can be used in many countries. The goal of the research is to determine the correlations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The findings underline the importance of self-efficacy, particularly physical self-efficacy, within the military context and its relevance in the psychological preparation of military personnel. Furthermore, it emphasizes the potential for exploring the role of physical activities in psychological preparation through the utilization of valid instruments (Fernate et al, 2019). The current study underscores the importance of considering self-efficacy in the design of interventions and training programs to enhance the effectiveness of soldiers in demanding and challenging military environments.…”
Section: Discussionmentioning
confidence: 84%
“…The findings underline the importance of self-efficacy, particularly physical self-efficacy, within the military context and its relevance in the psychological preparation of military personnel. Furthermore, it emphasizes the potential for exploring the role of physical activities in psychological preparation through the utilization of valid instruments (Fernate et al, 2019). The current study underscores the importance of considering self-efficacy in the design of interventions and training programs to enhance the effectiveness of soldiers in demanding and challenging military environments.…”
Section: Discussionmentioning
confidence: 84%
“…We also found that GPAQ has a stronger correlation with VO2Max than IPAQ and there was significant moderate positive correlation between GPAQ and IPAQ. Fernate et al, (2019) did a study to determine the correlation between the measurement attributes of the self-reported physical activity indicators in the Global Physical Activity Questionnaire (GPAQ), the International Physical Activity Questionnaire (IPAQ), and the European Health Survey Physical Activity Questionnaire (EHISPAQ) for 70 gym clients aged 18 to 70 years, and evaluate them simultaneously effective. The result of the study was all three questionnaires was significantly correlated.…”
Section: Figure 2 Correlation Matrix Among Ipaq Gpaq and Vo2maxmentioning
confidence: 99%